Guiding Light: Selections From the Holy Qur’an (American Journal of Islam and Society, 1987)
TranslationIn the name of Allah, Most Gracious,Most Merciful.102. O ye who believe!Fear God as He should be. . . .Surah 3208. O ye who believe!Enter into Peace [Islam]Whole-heartedly: . . .Surah 2135. O ye who believe!Stand out firmlyFor justice, as witnessesTo God, even as againstYourselves, or your parents,Or your kin, . . .Surah 4267. O ye who believe!Give of the good thingsWhich ye have (honourably) earned,And of the fruits of the earthWhich We have producedSurah 2 ...